(untitled) (Journal of the Spanish Institute for Strategic Studies, 2019)
The Member States of the European Union (EU) must assume the responsibility of their Defense and Security in an atmosphere defined by the existence of new threats, a lesser presence on the part of the United States, and the structural challenge that Brexit poses. The loss of military capabilities since the beginning of the crisis makes defense cooperation essential; this has materialized in a recent boost to the Common Security and Defense Policy (CSDP), which has recovered tools such as the Permanent Structured Cooperation (PESCO). Within this context, Portugal and Spain have put forward a new, constructive and convergent bilateral defense cooperation project that is a model of understanding. Through analysis of the possibilities, evolution, justification and importance of the model proposed, this article identifies the key points for the creation of mutually beneficial bilateral defense cooperation that would contribute to the strengthening of European defense.